2021
DOI: 10.1093/nar/gkab582
|View full text |Cite
|
Sign up to set email alerts
|

The phase separation-dependent FUS interactome reveals nuclear and cytoplasmic function of liquid–liquid phase separation

Abstract: Liquid–liquid phase separation (LLPS) of proteins and RNAs has emerged as the driving force underlying the formation of membrane-less organelles. Such biomolecular condensates have various biological functions and have been linked to disease. The protein Fused in Sarcoma (FUS) undergoes LLPS and mutations in FUS have been causally linked to the motor neuron disease Amyotrophic Lateral Sclerosis (ALS-FUS). LLPS followed by aggregation of cytoplasmic FUS has been proposed to be a crucial disease mechanism. Howev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 98 publications
(123 reference statements)
7
63
1
1
Order By: Relevance
“…Hoell et al reported that the TLS/FUS R521G mutant had a different RNA binding profile compared to WT in HEK293 cells [38], but they also claim that this was probably be due to mislocalization of the TLS/FUS mutant to the cytoplasm. In addition, a recent study revealed that TLS/FUS changes its interactome depending on its state, diffused or aggregated via LLPS [39]. Even in our in vitro experiment, R495X mutant exhibited the lowest specificity to the RNAs examined in this study, which implies NLS of TLS/FUS determines the specificity of RNA binding.…”
Section: Discussioncontrasting
confidence: 46%
“…Hoell et al reported that the TLS/FUS R521G mutant had a different RNA binding profile compared to WT in HEK293 cells [38], but they also claim that this was probably be due to mislocalization of the TLS/FUS mutant to the cytoplasm. In addition, a recent study revealed that TLS/FUS changes its interactome depending on its state, diffused or aggregated via LLPS [39]. Even in our in vitro experiment, R495X mutant exhibited the lowest specificity to the RNAs examined in this study, which implies NLS of TLS/FUS determines the specificity of RNA binding.…”
Section: Discussioncontrasting
confidence: 46%
“… (E) Overlaps between the HEK293 SG core proteomic dataset from the current study and published SG datasets. (F) Overlaps between the mFA core proteome and published human FUS protein interactomes ( Reber et al, 2021 ; Sun et al, 2015 ) and functional assignment of the proteins common for the three datasets ( n = 31). (G) Overlaps between the mFA core proteome and published interactomes of phase-separated/aggregated FUS species ( Kamelgarn et al, 2018 ; Reber et al, 2021 ) and functional assignment of the mFA proteins appearing in at least one of these two published interactomes ( n = 92).…”
Section: Resultsmentioning
confidence: 99%
“… (F) Overlaps between the mFA core proteome and published human FUS protein interactomes ( Reber et al, 2021 ; Sun et al, 2015 ) and functional assignment of the proteins common for the three datasets ( n = 31). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, similar effects were observed: GRN overexpression could reduce the accumulation of insoluble TDP-43, slow down the axonal loss and improve survival of mutant TDP-43 mice, but was ineffective in mutant SOD1 mice (Herdewyn et al, 2013;Beel et al, 2018). Motor neuron defects in zebrafish caused by FUS mutants or by loss of SMN1, could be rescued by GRN as well (Chitramuthu et al, 2010(Chitramuthu et al, , 2017.…”
Section: Grn As a Therapeutic Target In Neurological Diseasesmentioning
confidence: 60%